2015
DOI: 10.4315/0362-028x.jfp-14-321
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella on Basil Plants and in Pesto

Abstract: Leafy greens, including fresh herbs, have repeatedly been involved in outbreaks of foodborne disease. Although much effort has been put into studying leafy greens and products such as head lettuce and baby leaves, less is known about fresh leafy herbs, such as basil. The goal of this study was to investigate the survival of Salmonella on basil plants and in pesto. A mix of three Salmonella strains (Reading, Newport, and Typhimurium) was inoculated onto basil leaves and pesto and survived during the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…L. monocytogenes did not proliferate in the refrigerated RTE pesto formulation prepared in this study (pH 4.87, a w 0.891), but did survive, which is consistent with other studies [38,39]. Similar results were observed with S. enterica in pesto (pH 5.5, a w 0.28-0.30) during four-day storage at 4˚C where the rate of decline of the pathogen was 0.29 log CFU/g per day [40]. L. monocytogenes survival was also examined in two components of pesto, basil and garlic, in this study.…”
Section: Plos Onesupporting
confidence: 91%
“…L. monocytogenes did not proliferate in the refrigerated RTE pesto formulation prepared in this study (pH 4.87, a w 0.891), but did survive, which is consistent with other studies [38,39]. Similar results were observed with S. enterica in pesto (pH 5.5, a w 0.28-0.30) during four-day storage at 4˚C where the rate of decline of the pathogen was 0.29 log CFU/g per day [40]. L. monocytogenes survival was also examined in two components of pesto, basil and garlic, in this study.…”
Section: Plos Onesupporting
confidence: 91%
“…For Salmonella enterica , previously reports on the survival of Salmonella Newport ( Gorbatsevich et al, 2013 ) and a mix of Salmonella Reading, Newport, and Typhimurium ( Eckner et al, 2015 ) on growing (thus pre-harvest) basil plant leaves are available in literature. Despite of different experimental set-ups, both studies only observed a decline of Salmonella population on basil leaves and suggested a lack of growth.…”
Section: Discussionmentioning
confidence: 99%